The Transformation of Social Identity of the Young Generation in the Digital Era: Sociological and Cultural Anthropology Perspectives - Yorman; Evi Safitri Yulandari; Baiq Yulia Kurnia Wahidah (International Journal of Social Sciences and Humanities, 2025)
The development of digital technology has a significant impact on the formation of the social identity of the younger generation. Social media, digital spaces, and virtual culture are becoming new arenas where individuals construct, negotiate, and display their identities. This article aims to analyze the transformation of the social identity of the young generation in the digital era through sociological and cultural anthropological approaches. This study focuses on how interactions in virtual spaces shape patterns of communication, self-representation, and social relationships that are different from traditional patterns. This study uses a qualitative method based on literature studies and phenomenological observations on the behavior of the young generation on social media. The results show that digitalization drives a shift in values, where identity is no longer static, but fluid, plural, and often determined by algorithms and global popular culture dynamics. The identity of the younger generation is increasingly influenced by digital practices such as self-branding, the use of visual symbols, and participation in online communities. However, this transformation also raises paradoxes: on the one hand it expands the space of freedom of expression, but on the other hand increases vulnerability to cultural homogenization, social pressures and crises of authenticity. This article concludes that the transformation of social identity in the digital age must be understood as a continuous negotiation process between local values, globalization, and the influence of technology. The implications of this study emphasize the importance of digital literacy and cultural awareness as a strategy to strengthen the identity of the young generation to remain critical, reflective, and adaptive in the face of rapid social change.